2016
DOI: 10.1038/ncomms11428
|View full text |Cite
|
Sign up to set email alerts
|

A genetic basis for the variation in the vulnerability of cancer to DNA damage

Abstract: Radiotherapy is not currently informed by the genetic composition of an individual patient's tumour. To identify genetic features regulating survival after DNA damage, here we conduct large-scale profiling of cellular survival after exposure to radiation in a diverse collection of 533 genetically annotated human tumour cell lines. We show that sensitivity to radiation is characterized by significant variation across and within lineages. We combine results from our platform with genomic features to identify par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 71 publications
(84 reference statements)
3
133
2
Order By: Relevance
“…There is substantial evidence that clinical radiosensitivity in otherwise phenotypically normal cancer patients has a (largely) genetic basis (4,5). We and others have taken different approaches in an attempt to discern which genes may be responsible.…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence that clinical radiosensitivity in otherwise phenotypically normal cancer patients has a (largely) genetic basis (4,5). We and others have taken different approaches in an attempt to discern which genes may be responsible.…”
Section: Introductionmentioning
confidence: 99%
“…The XRCC1 CNV has been shown as a potential risk factor of radiation-induced toxicities in prostate cancer (Coates et al , 2015). Large-scale profiling of 533 genetically annotated human tumor cell lines identified several genetic features (somatic copy number alterations, gene mutations and basal mRNA expression) that regulate survival after exposure to radiation (Yard et al , 2016). These included functionally important genes in cell cycle regulation ( E2F1 ), chromosome maintenance ( KIF3B ), glutathione synthesis ( GSS ) and apoptosis ( BCL2L1 ).…”
Section: Radiogenomics Overviewmentioning
confidence: 99%
“…Alternatively, rather than searching for signatures, which don’t explain underlying radiobiology, mRNA panels can be used to further explore and elucidate the mechanisms by which certain cancers exhibit radiosensitivity or resistance – examples of such cases include the well-known National Cancer Institute (NCI) mRNA expression panel (Kim et al , 2012). The study by Yard et al revealed gene expression sets that correlated with radiation sensitivity including DNA damage response, cell cycle, chromatin organization and RNA metabolism while genes that correlated with radiation resistance included cellular signaling, lipid metabolism and transport, stem-cell state, cellular stress and inflammation (Yard et al , 2016). …”
Section: Radiogenomics Overviewmentioning
confidence: 99%
“…39,40 This approach has defined a variety of genes that may be involved in radiosensitivity of different tumour cell populations, but there are various limitations to such studies, notably the use of high throughput analyses of radiation response of the cells, which limits the ability of the studies to examine genetic factors separately affecting the low-dose vs the high-dose region of the survival curve. Other concerns with such studies can relate to the potential selection bias associated with the growth of cells in vitro (if cell lines are used in the study) or the potential role of heterogeneity and multiple clones within tumours (if biopsies are used in the study).…”
Section: Retrospectivementioning
confidence: 99%
“…These issues may also be a concern for studies trying to identify genetic changes in which large numbers of cancer cell lines are examined for correlations between genetic or epigenetic abnormalities associated with radiation response. 40 The findings of such studies will need careful follow-up in appropriate models before they can be used for personalizing radiation treatment strategies. Recent studies in primary tumours have, however, identified genomic instability as a driver of disease aggressiveness and treatment failure in both surgical and radiation treatment of prostate cancer.…”
Section: Future Studiesmentioning
confidence: 99%